Gender view to the Republic of Tyva - Tulush, Milada N. (The New Research of Tuva, 2014)
Article presents the generalized research of contemporary demographic processes in the Republic of Tyva. Analysis performed on the basis of Tyvastat data and the results of All-Russian census.
Keywords: Tyvastat; statistics; gender; demographic processes